Legal Analysis of The Application of Article 303 Paragraph (1) to 1 KUHP of The Criminal Code in Online Gambling Cases Study of Decision Number 283/PID.B/2024/PN Rokan Hilir - Pramanda Gustiadi; Nimrot Siahaan; Ahmad Ansyari Siregar (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Technological advancements have given rise to new crime modalities, including online gambling. Law enforcement against these practices often utilizes provisions in the Indonesian Criminal Code (KUHP), which does not explicitly regulate online gambling. This research analyzes the application of Article 303 Paragraph (1) point 1 of the KUHP in the Decision of the Rokan Hilir District Court Number 283/PID.B/2024/PN Rokan Hilir. The research method used is normative juridical with a case study approach. The results indicate that the application of the aforementioned article to the online gambling perpetrator was appropriate, even though the formulation of the article does not specifically mention online gambling. The judge argued that the substance of the defendant's actions, namely acting as a bookie, had fulfilled the elements of Article 303 Paragraph (1) point 1 of the KUHP. This decision sets an important precedent that Indonesian positive law can reach conventional crimes that migrate into the digital space.